2003
DOI: 10.1021/la034160a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Crystalline and Amorphous Palladium Nanoparticles

Abstract: Ligand-stabilized palladium amorphous nanoparticles with various monodispersed sizes ranging from 2 to 6 nm were synthesized and compared with palladium crystalline nanoparticles. The nanoparticles were characterized by high-resolution electron microscopy (HREM), X-ray photoelectron spectroscopy, and scanning tunneling microscopy/spectroscopy (STM/STS). Both HREM images and electron diffraction patterns show quite clear differences in structures between crystalline and amorphous palladium nanoparticles. STS sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 37 publications
7
48
0
2
Order By: Relevance
“…It was observed that the lower the temperature used, the greater the crystallinity of the nanoparticles. They explained this behavior with the same arguments as Hou et al; 19,20 i.e., low temperatures decrease the reaction rates, which leads to an ordered packing of palladium atoms. However, it is also possible that the chemical nature of the ligand−metal bond changes at different temperatures.…”
Section: ■ Introductionmentioning
confidence: 54%
“…It was observed that the lower the temperature used, the greater the crystallinity of the nanoparticles. They explained this behavior with the same arguments as Hou et al; 19,20 i.e., low temperatures decrease the reaction rates, which leads to an ordered packing of palladium atoms. However, it is also possible that the chemical nature of the ligand−metal bond changes at different temperatures.…”
Section: ■ Introductionmentioning
confidence: 54%
“…In a previous study, we found that Au‐NPs with sizes of ≈3 nm are crystalline 19. However, Lu et al28 recently demonstrated that amorphous palladium‐nanoparticles (Pd‐NPs) can be synthesized. We have studied the crystal structure of the generated Au‐NPs by HR‐TEM and WAXS.…”
Section: Resultsmentioning
confidence: 95%
“…In general low metal concentrations are employed [4], but also the use of low-boiling organic solvents [5], high temperatures [6], very fast addition of reagents [7], or the use of reagents that are expensive or not commercially available [8] makes their production on an industrial scale difficult.…”
Section: Introductionmentioning
confidence: 99%